Promoters with the octamer DNA motif (ATGCAAAT) can be ubiquitous or cell type-specific depending on binding affinity of the octamer site and Oct-factor concentration. - Kemler, I (1991)
Immunoglobulin (Ig) gene promoters contain the octamer sequence motif ATGCAAAT which is recognized by cellular transcription factors (Oct factors). Besides the ubiquitous Oct-1 factor, there is also a group of related factors (Oct-2 factors) encoded by a separate gene. The Oct-2 gene is regulated in a cell-type specific manner, and the protein is present in large amounts in B lymphocytes. We have previously shown that simple composite promoters of an octamer/TATA box type are poorly active in non-B cells but are strongly responsive to ectopic expression of Oct-2A factor, a major representative of the lymphocyte Oct-2 factors. In the present study we have tested the activity of a number of composite promoters and natural Ig promoters, and their response to Oct-1 and Oct-2 factors. Unexpectedly, we find that octamer/TATA promoters with a high affinity octamer site direct ubiquitous expression. By contrast, promoter constructions that behave in a B cell-specific manner tend to have a weak octamer binding site. These promoters are responsive to ectopic expression of additional Oct-factor, irrespective of whether it is Oct-1 or Oct-2. Using natural Ig promoters rather than composite promoters, we find that an IgH promoter is well transcribed in non-B cells via the ubiquitous Oct-1 factor, while Ig kappa and Ig lambda light chain promoters require additional Oct factor for maximal expression. It seems therefore likely that during B cell differentiation, Ig heavy chain promoters can be activated by Oct-1, before the appearance of Oct-2 factors. Oct-2 factors then would serve to boost the expression from Ig light chain promoters, which are known to be activated only after successful heavy chain gene rearrangement.